The importance of pharmaceutical care in the prevention and treatment of patients with type 2 diabetes mellitus: Literature review (Research, Society and Development, 2022)
To confirm the importance of pharmaceutical professionals in the treatment of diabetes, the aim of this study is to identify the relevant literature, pharmaceutical care provided to patients with type 2 diabetes. This is an integrative review of the literature using data sources such as Scielo, Pubmed and Lilacs. Type 2 Diabetes Mellitus is a metabolic disease that has been increasing in recent years due to the sedentary lifestyle that many people have adopted. In addition to an inadequate diet, this population group should use oral hypoglycemic agents or insulin to keep their glucose levels within normal limits. The pharmacist is a trained professional who can advise on pharmaceutical and non-pharmaceutical treatments as well as all drug interactions. It was understood that it is essential that pharmaceutical care be performed continuously to diabetic patients, because many of them develop secondary diseases related to inadequate use of medications, because they do not present adequate pharmacological responses or present adverse drug reactions.